Grimm vs. Disney in the battle for children's ideologies - Ang, Rachel Hui Ying (2012)
Although Disney’s adaptation of Snow White and the Seven Dwarfs has demonstrated how plot and character details are altered in order to suit the ideology of his audience in 20th century America, the Grimm brothers, who are often mistakenly seen as authors of the ‘original’ fairy tales, were as guilty of tweaking narratives to cater to the demands of the 19th century German bourgeoisie. Adults throughout the centuries up until today have had varying opinions on the different messages encoded within both the Grimm and Disney renditions. However, their motivation for analysing and critiquing such literary productions is the concern that the worldview of the author or producer, demonstrated in these narratives, in turn influences the development of the worldview of the children who encounter it. As a result, adults tend to be anxious when they identify messages that are deemed potentially detrimental to the formation of children’s morality, worldview and ideology, particularly over traumatic elements such as portrayals of violence, and strive to protect and preserve the assumed state of angelic innocence of children for as long as possible by censoring these elements. This sentimentalised image of childhood has been built up through the ages by philosophies on childhood, with most adults subscribing to the idea that childhood is a stage of innocence and transcendence of socially imposed limitations and responsibilities. In the light of the severe criticism that children’s literature, such as the Grimm and Disney tales, has been put through, it is also nostalgia and defensiveness of this freedom that adults believe children to possess. One must realise that it is impossible to remain within this state forever, and instead of jumping to conclusions regarding the value of a tale, to see what the individual child needs. For, like the fairy tale, each person is perpetually changing, and requires stories that do so as well.